Можливість компенсації гіпотиреозу шляхом аутотрансплантації фрагментів тиреоїдної тканини у хворих із багатовузловим зобом після тиреоїдектомії - Товкай, О. А.; Ларін, О. С.; Черенько, С. М. (Clinical Endocrinology and Endocrine Surgery, 2009)
We propose the simple method of short term preservation of thyroid tissue during 5-7 days after an operation for its free autotransplantation immediately after favourable pathological report as a perspective preventive way of postoperative hypothyroidism for patients with multinodular goiter. During 2002-2006 years the auto transplantation of thyroid tissue fragment in the early postoperative period was executed in 57 patients with multinodular goiter. In this case a volume of operation amounted to thyroidectomy. Natural hormones which were synthesized by the autotransplantat compensate significantly and more effective the failed thyroid function regardless of body requirements in exogenic thyroxine.